Improving Medication Uptake in Aboriginal and Torres Strait Islander Peoples - Davidson, Patricia; Abbott, P.; Davison, J.; Digiacomo, Michelle (Elsevier, 2010)
Background: Poor medication adherence is associated with adverse health outcomes. Improving access and adherence to pharmacological therapy is important in achieving optimal health outcomes for Indigenous populations. In spite of the impressive evidence base for cardiovascular pharmacotherapy, strategies for promoting adherence and evidence based practice are less well refined and the challenges for Indigenous populations are more pronounced. Aim: To identify factors impactingonmedication adherence in Aboriginal Australiansandidentify solutions to improve the quality use of medicines. Method: The World Health Organization adherence model was used to classify barriers to adherence. Key elements of this model are (1) health care team/health system; (2) socio-economic factors; (3) therapy; (4) patient; and (5) condition related. Results: Entrenched socio-economic differentials aggravate challenges to medication adherence amongst Aboriginal Australians. Initiatives to promote the quality use of medicines, such as the Quality Use of Medicines Maximised for Aboriginal and Torres Strait Islander People (QUMAX) Program, are important strategies to promote adherence. Conclusions: Medication adherence is a complex issue and addressing modifiable factors is imperative to improve health outcomes. Subsidised access to medications whether living in urban, regional, rural or remote areas is an important strategy in Closing the Gap.